Food waste composting at school - George, Steafanie; Mohd Kamil, Nor Amani Filzah; Abdul Kadir, Aeslina (Penerbit UTHM, 2020)
Abstract Saving the earth and maintaining sustainability are some of the efforts and concept that’s becoming popular. The majority have started to reuse and recycle plastic containers, and aluminium cans to reduce environmental issues on earth. However, organic waste such as food waste, grass and leaves are included in the waste issue and contributed about 60% of it. Nevertheless, these organic wastes are totally recyclable, and that is where the composting concept takes place. This chapter describes on activities of food waste composting that can be implemented in school. This chapter also describes the outcome of the composting activities to students, teachers and other staffs in school, especially working in the canteen area.